Investigation of Dose Falloff for Intact Brain Metastases and Surgical Cavities Using Hypofractionated Volumetric Modulated Arc Radiotherapy. (February 2016) - Ruschin, Mark; Lee, Young; Beachey, David; Yeboah, Collins; Wronski, Matt; Babic, Steven; Lochray, Fiona; Nico, Anula; Khan, Luluel; Soliman, Hany; Sahgal, Arjun
Introduction: Intact brain metastases tend to be small and spherical compared to postsurgery brain cavities, which tend to be large and irregular shaped and, as a result, a challenge with respect to treatment planning. The purpose of the present study is to develop guidelines for normal brain tissue dose and to investigate whether there is a dependence on target type for patients treated with hypofractionated volumetric modulated arc radiotherapy (HF-VMAT). Methods: Treatment plans from a total of 100 patients and 136 targets (55 cavity and 81 intact) were retrospectively reviewed. All targets were treated with HF-VMAT with total doses ranging between 20 and 30 gray (Gy) in 5 fractions. All plans met institutional objectives for organ-at-risk constraints and were clinically delivered. Dose falloff was quantified using gradient index (GI) and distance between the 100% and 50% isodose lines (R50). Additionally, the dose to normal brain tissue (brain contour excluding all gross tumor or clinical target volumes) was assessed using volume receiving specific doses (Vx) where x ranged from 5 to 30 Gy. Best-fit curves using power law relationships of the form y = ax b were generated for GI, R50, and Vx (normal brain tissue) versus target volume. Results: There was a statistically significant difference in planning target volume (PTV) for cavities versus intact metastases with mean volumes of 37.8 cm 3 and 9.5 cm 3, respectively ( P < .0001). The GI and R50 were statistically different: 3.4 and 9.8 mm for cavities versus 4.6 and 8.3 mm for intact metastases ( P < .0001). The R50 increased with PTV with power law coefficients (a, b) = (6.3, 0.12) and (5.9, 0.15) for cavities and intact, respectively. GI decreased with PTV with coefficients (a, b) = (5.9, −0.18) and (5.7, −0.14) for cavities and intact, respectively. The normal brain tissue Vx also exhibited power law relationships with PTV for x = 20 to 28.8 Gy. In conclusion, target volume is the main predictor of dose falloff. The results of the present study can be used for determining target volume-based thresholds for dose falloff and normal brain tissue dose–volume constraints.